Ascaris exit through the feeding jejunostomy tract: A rare case report - Mohd Lateef WANI; Ajaz Ahmad RATHER; Ifat IRSHAD; Zubair Ashraf HAKEEM; Akram Hussain BIJLI; Tahir Saleem KHAN; Reyaz Ahmad LONE (Turkish Journal of Gastroenterology, 2019)
-